Kindergarten Class Graduation at Jackson Elementary School - Watkins, Howard::::::::: (1984)
Principal Ruben Barrios and teacher LeAnne Wiens presenting certificate to Devon Bleile-Kratzer Devon wearing red shorts and white sandals